2008
DOI: 10.5194/angeo-26-955-2008
|View full text |Cite
|
Sign up to set email alerts
|

Transient and localized processes in the magnetotail: a review

Abstract: Abstract. Many phenomena in the Earth's magnetotail have characteristic temporal scales of several minutes and spatial scales of a few Earth radii (R E ). Examples of such transient and localized mesoscale phenomena are bursty bulk flows, beamlets, energy dispersed ion beams, flux ropes, traveling compression regions, night-side flux transfer events, and rapid flappings of the current sheet. Although most of these observations are linked to specific interpretations or theoretical models they are inter-related … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
94
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 123 publications
(100 citation statements)
references
References 228 publications
(347 reference statements)
5
94
1
Order By: Relevance
“…Alternatively, during a slip-type deformation, the flux tubes shift vertically relative to their neighbors, but the magnetic field orientation remains the same, irrespective of the normal direction and the sheet tilt. Quiet-time stronglytilted sheets, forming a significant subset of Cluster flapping events, were consistent with a slip-type displacement (see also Sharma et al, 2008). A good example is the 3 August 2004 event (Fig.…”
Section: Introductionmentioning
confidence: 78%
“…Alternatively, during a slip-type deformation, the flux tubes shift vertically relative to their neighbors, but the magnetic field orientation remains the same, irrespective of the normal direction and the sheet tilt. Quiet-time stronglytilted sheets, forming a significant subset of Cluster flapping events, were consistent with a slip-type displacement (see also Sharma et al, 2008). A good example is the 3 August 2004 event (Fig.…”
Section: Introductionmentioning
confidence: 78%
“…The filamentary nature of CSs has been predicted theoretically by Lee & Fu (1985) and Lee (1995) and confirmed by CLUSTER observations in the magnetotail (e.g., Slavin et al 2003Slavin et al , 2005Eastwood et al 2005): plasmoids observed by CLUSTER well fit a scenario of multiple X-lines where reconnection takes place and produces plasmoids. Observations have also shown that one of the many X-lines, for so far unknown reasons, becomes dominant (Sharma et al 2008).…”
Section: Cs Inhomogeneitiesmentioning
confidence: 99%
“…However, other manifestations of CS dynamics (e.g. earthward plasma flows with dipolarisation fronts, formation of plasmoids) are also observed (Sharma et al, 2008;Baumjohann et al, 2007). One can distinguish two kinds of flapping motion: the vertical oscillations of the quasi-horizontal CSs (when the normal N to the CS plane is basically along the z axis, |N z | > 0.8, and kink-like waves do not propagate) and formation of tilted CSs (when the normal is significantly tilted, |N z | < 0.8, and kink-like waves can propagate along the dusk-dawn direction) (see details of this classification in Rong et al, 2015).…”
Section: Introductionmentioning
confidence: 99%